PENGARUH GARAM TERHADAP HASIL PENCELUPAN BAHAN SUTERA DENGAN EKSTRAK KULIT POHON MAHONI - Derisa, Derisa; Efi, Agusti; Adriani, Adriani (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2012)
The purpose of this study to reveal the resulting color dyeing silk using mahogany bark extract using a ratio much salt 10 grams, 30 grams and 60 grams, and the difference in outcomes dyeing (color, value, color and flatness). This type of research is experimental research. The variables of this study is the variable X as a control, the independent variables are X1, and Y variables dyeing color difference results (value and flatness of color). Types of data used are primary data. Sources of data in this study was a faculty department UNP KK FT 5 people and students by 5 people. Mechanical analysis of data processed and compiled, and analyzed by one-way analysis of variance. Processed using SPSS version 12.0. Based on the analysis of variance of data on the color (hue) colors obtained landing leads to Yellowish brown (peru), with the addition of 10 grams of salt leads to a brown color (Chocolate), 30 grams of salt leads to a young brown color (Sienna), and 60 grams of salt leads to a young brown color (Sienna).